2019
DOI: 10.9778/cmajo.20190026
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis use during methadone maintenance treatment for opioid use disorder: a systematic review and meta-analysis

Abstract: T he opioid epidemic related to an increase in prescriptions [1][2][3][4] has escalated in the past 2 decades. Opioid use disorder is a fundamental component of this crisis. 5,6 Despite the morbidity and mortality due to opioid use disorder, high rates of HIV infection and hepatitis C among patients with the disorder and high unemployment rates, treatment options are limited in scope and effectiveness. 7,8 Methadone maintenance therapy is the most common treatment for opioid use disorder, 9,10 although other t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(53 citation statements)
references
References 58 publications
0
53
0
Order By: Relevance
“…Among the participants using cannabis during follow up, 38.5% used cannabis in combination with another substance, majority using cannabis together with heroin. This pattern of polysubstance is common in patients on methadone therapy (14). Additionally, majority of those using cannabis at intake, continued use during follow up and were more likely to be lost to follow up compared to cannabis non-users.…”
Section: Prevalence and Pattern Of Cannabis Usementioning
confidence: 94%
See 3 more Smart Citations
“…Among the participants using cannabis during follow up, 38.5% used cannabis in combination with another substance, majority using cannabis together with heroin. This pattern of polysubstance is common in patients on methadone therapy (14). Additionally, majority of those using cannabis at intake, continued use during follow up and were more likely to be lost to follow up compared to cannabis non-users.…”
Section: Prevalence and Pattern Of Cannabis Usementioning
confidence: 94%
“…Polysubstance use is common among patients on methadone maintenance treatment globally with cannabis being the most frequently used drug in this population. In addition, prevalence of cannabis use in patients on methadone maintenance treatment is higher than the prevalence in the general population (14). Some studies have reported a high prevalence ranging at 50-70% (15,16).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…58 Most recently, a 2019 systematic review and meta-analysis of adults with opioid use disorder found no effect of cannabis use in opioid use. 59 Therefore, findings on this topic continue to be too mixed and scarce to allow strong conclusions.…”
Section: Tolerance and Other Drug Usementioning
confidence: 99%